Slavenski mitski trokut i legenda o Kamenim svatima The Slavic Mythical Triangle and the Legend about Kameni svati (Petrified Wedding Guests) - Đermek, Anđelko (Studia mythologica Slavica, 2009)
<span style="line-height: 115%; font-family: ’Calibri’,’sans-serif’; font-size: 11pt; mso-ansi-language: EN-US; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: ’Times New Roman’; mso-bidi-theme-font: minor-bidi; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">The legend of wedding guests who were turned to stone is interpreted as an echo of the Slavic myth about the incestuous wedding of Mare and Jarilo, the divine twins. The myth had been reconstructed by V. Belaj and R. Katičič. In the vicinity of Kameni svati there is a complex of sacred triangles clustered around the toponym Babožnica. Beside the previously mentioned angle of 23.5° the author of this article also defines the angle that represents a deviation between the azimuth of the sun setting (or rising) on the equinoxes and the solstices. Suggesting that the traditional custom of building artificial trees for bonfires and the huts is connected to the sacred tree as described in Vita Otonis, the author proves that these were the very structures that had once been situated on the pinnacles of the sacred triangle.